Unlocking the regulatory code of RNA: launching the Human RNome Project - Adams, Mark; Boileau, Etienne; Bujnicki, Janusz M.; Cheung, Vivian G.; Conticello, Silvestro G.; Dedon, Peter; Dieterich, Christoph; Gallo, Angela; Göke, Jonathan; Helm, Mark; Jantsch, Michael F.; Kaiser, Stefanie; et al. (Genome biology, 2025)
The human RNome, the complete set of RNA molecules in human cells, arises through complex processing and includes diverse molecular species. While research traditionally focuses on four canonical nucleotide residues, the RNome, encompassing over 180 distinct modifications across organisms, with at least 50 in humans, is increasingly recognized. These modifications play critical roles in regulating RNA structure, stability, and function, yet the rules linking their precise locations to biological outcomes remain poorly defined. The Human RNome Project aims to map all RNA modifications, build essential resources, and harness new technologies to transform RNA biology, therapeutic development, agriculture, and even data storage.
Veröffentlicht: 24. Oktober 2025
*The International Human RNome Project Consortium: Mark D. Adams, Etienne Boileau, Janusz M. Bujnicki, Vivian G. Cheung, Silvestro G. Conticello, Peter Dedon, Christoph Dieterich, Angela Gallo, Jonathan Göke, Mark Helm, Michael F. Jantsch, Stefanie Kaiser, Charles Lee, Virginie Marchand, Ali Mortazavi, Yuri Motorin, Schraga Schwartz, Blanton S. Tolbert, James Williamson
Gesehen am 19.12.2025